(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay analyses whether and if it is possible for the European Union to protect the abortion. Starting from the ban on abortion in Poland, the reaction of EU will be examined. Due to the fact that abortion does not fall within the competence of the Union, any guarantee must involve the protection of human rights as fundamental values of the EU; it is therefore necessary to establish whether abortion can be classified as a human right under international law. A reflection follows on the ways European law offers to preserve abortion and whether the introduction of art. 7bis in EU Charter could enforce the protection of legal and safe abortion in all member States.